Tarja magazine: A task accomplished - Bruce, Beatriz (2021)
Tarja magazine, published in the north of Argentina between 1955 and 1960, is a good example of a regional literary publications considered the first important cultural and artistic magazine of that region. It is an expression of identity of its time and a milestone in Latin America.